The influence of transformational leadership style on ICT adoption in the Nigerian construction industry - Waziri, Abdullahi Y. (Canadian Center of Science and Education, 2015)
Information and communication technology provides construction organizations with new opportunities for improving the process of collaboration, managerial functions and maintenance of competitive advantage. Its adoption has however been faced with problem of incompetent organizational leadership. The purpose of this study, therefore, is to examine the influence of transformational leadership style on IT adoption in construction organizations. Structural equation modelling analytical approach was used to test the presence of a positive and direct relationship between transformational leadership style and IT adoption in organizations. Results strongly supported the hypothesis of a positive and direct relationship with a path coefficient of.79. Part of the recommendation of the study was for managers to diligently exhibit transformational leadership behaviours during technological change in their organizations by paying attention to the needs of their employees, providing ways and reasons for employees to comprehend and analyse problems in different ways, adequate employee motivation and building confidence and trust with employees.